Reactions of acryl thioamides with iminoiodinanes as a one-step synthesis of N-sulfonyl-2,3-dihydro-1,2-thiazoles - Vladimir G. Ilkin; Pavel S. Silaichev; Valeriy O. Filimonov; Tetyana V. Beryozkina; Margarita D. Likhacheva; Pavel A. Slepukhin; Wim Dehaen; Vasiliy A. Bakulev (Beilstein Journal of Organic Chemistry, 2025)
A one-step method has been developed for the preparation of 2,3-dihydro-2-sulfonyl-3,4,5-substituted 1,2-thiazoles by the reaction of acryl thioamides and iminoiodinanes. A library of 31 examples of tetrasubstituted 1,2-thiazoles was thus synthesized in high yields. The effectiveness of the synthesis method for these poorly studied 1,2-thiazoles was confirmed by scaling the reaction using gram amounts of the starting thioamide.